IDIOMA E IDENTIDAD EN EL NOVO CINEMA GALEGO - Ddo. Brais ROMERO SUÁREZ (Fonseca, Journal of Communication, 2023)
The talk of town since its inception in 2010, the Cinema Novo Galego has been successful in all competitions and festivals that has been present. From the FIPRESCI prize in Cannes to the Best Emerging Director at Locarno, this new wave of cinema places Galicia in the world film stage. But does Novo Cinema Galego an accurate representation of Galicia? What's the role of Galicia in this movement?